Factors Influencing Adherence to the Utilization of Personal Protective Equipment among Healthcare Workers: A Systematic Review - Ningsih, Atni Setiyo; Suryani, Dyah (Epidemiology and Society Health Review (ESHR), 2024)
Background: Hospitals as providers of health services for the community must be able to maintain the quality of services provided, one of which is by providing safety and comfort guarantees to officers from infectious diseases and other hazardous substances with policies regarding the use of personal protective equipment (PPE) and conducting evaluations from the behavior of officers when using PPE. Many factors affect the compliance of officers in the use of PPE. Purpose: The purpose of this study was to analyze the factors that influence the compliance of officers, especially nurses in using PPE. Method: This study uses a literature review method. Articles were collected from the online database from Pubmed from 2012 – 2023. Using the keywords “health worker compliance”, “nurse” and “personal protection equipment”. After entering the keywords, 238 articles were obtained and filtered again based on inclusion and exclusion criteria and 16 articles were obtained for review. Results: Internal factors that affect compliance of officers in the use of PPE include age, years of service, knowledge, attitudes, motivation while external factors that affect compliance are facilities, training and supervision carried out by management Conclusion: To increase officer compliance, it is necessary to have supervision and support from management in the form of facilities, ease of access and training